Strategi Pendidikan SMA Darul Ma’arif dan Peran Pemerintah dalam Menghadapi Krisis Literasi Nasional - Muniratri Rachmita; Elisabeth Hana G.S; Qonita Mutmainah; Sabina Namira Rachman; Subakdi Subakdi; Kayus Kayowuan Lewoleba; Abdul Halim; Andreas Bramantyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The national literacy crisis is a serious challenge for the education system in Indonesia. This research examines the educational strategies implemented at Darul Ma’arif High School in an effort to improve student literacy and analyzes the role of the government in supporting the improvement of literacy quality at the secondary school level. This research uses a qualitative approach with in-depth interview and observation methods to understand the learning strategies, infrastructure, and literacy programs implemented at Darul Ma’arif High School and through a community service approach in the form of socialization themed